39‐3: Patternable Color‐conversion Films based on Thick‐shell Quantum Dots. Issue 1 (2nd June 2017) - Lien, Jiun-Yi; Chen, Chih-Jung; Chiang, Ray-Kuang; Wang, Sue-Lein
Abstract : Thick‐shell quantum dots (QDs) with green and red emission as well as high absorbance values are fabricated and dispersed in a commercial photoresist with density larger than 20 wt %. Such QD‐photoresist composites enable next‐generation displays with high brightness and wide color gamut (> 90 % Rec. 2020 coverage) through traditional lithography process for color filters. The emissive QD‐color filters (QDCFs) with thickness below 6 μm show optical density (O.D.) above 0.9 and film quantum yield reaching 70 %. The patterned QDCFs with 20~40 wt % of QDs reach the minimum line width about 7 μm.